A Study on the Impact of Satisfaction with Public Libraries on Using and Recommending Intention - Noh, Younghee; Chang, Rosa (International Journal of Knowledge Content Development & Technology, 2020)
As the South Korean government has recently announced its intention to implement a three-year policy on building additional libraries and complex community centers as the community-based everyday life SOC project, society has shed new light on libraries as public service institutions. Accordingly, this study was conducted to determine the factors affecting resident satisfaction with public libraries, intention to use, and intention to recommend public libraries, for use as basic data to increase resident satisfaction and use of public libraries in South Korea. To this end, we conducted a survey on residents who have experience with using 13 public libraries designated as regional representative libraries in South Korea. The surveyed data was verified with structural equation using AMOS. The results were as follows. First, all factors, such as material, facility, staff, program, and service, except location and space, had a significant effect on resident satisfaction with public libraries. Second, it was found that satisfaction had a significant effect on intention to use and intention to recommend. The results of this study may contribute to qualitatively improving public library services by reflecting the changing needs of users, as well as social trends at the working level of libraries in the South Korean society. URL: http://ijkcdt.net/xml/24907/24907.pdf